Evaluation of histological and biomechanical properties on engineered meniscus tissues using sonication decellularization - Mohamad Ghazali, Aina Mardhiyah; Sha'ban, Munirah; Noor Azmi, Azran Azhim (Institute of Electrical and Electronics Engineers Inc., 2017)
Sonication decellularization treatment requires proper evaluations on its ability to decellularize meniscus tissue efficiently. This study was done to evaluate the histological and biomechanical properties within meniscus scaffolds. Van Gieson staining was done to evaluate the efficiency of cell removal in meniscus tissues. The consequences of treatment on viscoelastic properties are vital for scaffolds quality and were properly investigated. Picrosirius red and Safranin-O/Fast green staining was carried out to detect extracellular matrix materials (ECM). Sonication decellularization treatment has the ability to demonstrated complete nuclei removal compare to control samples as well as maintaining viscoelastic properties, namely stiffness, compression and residual force. Thus, sonication decellularization treatment had successfully produced and prepared a meniscus bioscaffold candidate in which its biomechanical strength is sustained through protection of ECM properties.